SEG 2017 Workshop: Full-Waveform Inversion and Beyond, Beijing, China, 20-22 November 2017 2017
DOI: 10.1190/fwi2017-007
|View full text |Cite
|
Sign up to set email alerts
|

3D wave-equation dispersion inversion of surface waves

Abstract: The 2D wave-equation dispersion inversion (WD) methodology is extended to the inversion of three-dimensional data for a 3D shear-wave velocity model. The objective function of 3D WD is the sum of the squared wavenumber differences along each azimuth angle between the predicted and observed 3D dispersion curves. The 3D dispersion curves are obtained by wavenumber-frequency analysis of the fundamental Rayleigh waves in each 3D shot gather. The S-wave velocity update is computed by a weighted zero-lag crosscorrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…(2016) and Liu et al. (2018) found the optimal S‐velocity model by using the dispersion curves associated with the surface waves. A comprehensive introduction to skeletonized inversion is presented in Lu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) and Liu et al. (2018) found the optimal S‐velocity model by using the dispersion curves associated with the surface waves. A comprehensive introduction to skeletonized inversion is presented in Lu et al.…”
Section: Introductionmentioning
confidence: 99%
“…problem (Virieux & Operto, 2009) and successfully recovers the background information of the model of interests: Schuster (1991a, 1991b) used wavefield correlations to invert the first arrival traveltime for the subsurface background velocity model, while Choi and Alkhalifah (2015) used a space-domain unwrapped phase with exponential damping to mitigate the nonlinearity associated with the reflections. Dutta and Schuster (2016) inverted for the Qp model by minimizing the central/peak frequency differences between the observed and predicted early arrivals; similarly, Li et al (2017) utilized the peak frequency shifts of the surface wave to invert for the Qs model; and Li et al (2016) and Liu et al (2018) found the optimal S-velocity model by using the dispersion curves associated with the surface waves. A comprehensive introduction to skeletonized inversion is presented in Lu et al (2017).…”
mentioning
confidence: 99%
“…We performed 1D inversions using a plane wave approximation for a 3D strucutre, which may cause some bias in the inverted velocity strucutre in the presence of strong lateral heterogeneities as noted in Wielandt (1993). In such cases a 3D wave-equation based inversion method could be used in future to improve the results (Li et al 2017;Liu et al 2018).…”
Section: Dispersion Inversion Using Energy Likelihood 23mentioning
confidence: 99%
“…In the 2D case, the azimuth angles have only two values: 0 • and 180 • , corresponding to the left and right directions, respectively. The gradient γ(x) of ε with respect to the S-wave velocity v s (x) is given in (Liu et al, 2017), which is computed using a weighted zero-lag correlation between the source and backward-extrapolated receiver wavefields.…”
Section: Theorymentioning
confidence: 99%
“…Wave-equation dispersion inversion (WD) of Rayleigh waves uses solutions to the 2D or 3D elastic-wave equation to invert the dispersion curves of surface waves for the S-velocity model (Li and Schuster, 2016;Li et al, 2016Li et al, , 2017aLiu et al, 2017). The advantage of WD over the traditional dispersion inversion method (Haskell, 1953;Xia et al, 1999Xia et al, , 2002Park et al, 1999) is that WD does not assume a layered velocity model and is valid when there are strong lateral gradients in the S-velocity model.…”
Section: Introductionmentioning
confidence: 99%